Pengembangan Penilaian dalam Berpikir Kritis Siswa melalui Soal Higher Order Thinking Skills (HOTS) pada Materi Jenis-jenis Historiografi di SMA Naudhatul Ulama Palembang - Arviansyah, Muhammad Reza; Febriyani, Siti Hilda; Zaskia, Farach Audi; Safitri, Sani; Putri, Ratu Ilma Indra (STKIP PGRI Bandar Lampung, 2023)
This research was conducted as an effort to develop HOTS-based questions which included discussions on Historiography (Traditional, Colonial, National and Modern). In this study applied quantitative research methods using research and development methods to find out and measure the level of students’ understanding of the use of Higher order thinking skills (HOTS) questions in the material types of historiography in history learning. The development research method is research that is used to test the level of success and effectiveness of a product, which in this case is based on the use of Higher Order Thinking Skills (HOTS) questions. This study also aims to see the results in the form of elaboration starting from the process to the results in the HOTS test questions tested, also to measure the level of development of the questions on the Historiographical types of material that have been tested before through verification of teaching staff, fellow students, and field tests so that later questions is valid and the results of this research data are also real.